2018
DOI: 10.1016/j.healun.2018.01.619
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of Frailty After Lung Transplantation

Abstract: Background. Frailty contributes to increased morbidity and mortality in patients referred for and undergoing lung transplantation (LTX). e study aim was to determine if frailty is reversible after LTX in those classified as frail at LTX evaluation. Methods. Consecutive LTX recipients were included. All patients underwent modified physical frailty assessment during LTX evaluation. For patients assessed as frail, frailty was reassessed on completion of the post-LTX rehabilitation program. Frailty was defined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…We have previously reported a PF prevalence of 24% in a cohort of patients undergoing LTX evaluation and 16%, as assessed pre-LTX, in a cohort of LTX recipients. 5,13 In our present study, the prevalence of PF was 22%, CogF 28%, DepF 29%, and ComF 34% in patients on the LTX waitlist. Second, PF, low serum albumin, and MCI are independently associated with waitlist mortality.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…We have previously reported a PF prevalence of 24% in a cohort of patients undergoing LTX evaluation and 16%, as assessed pre-LTX, in a cohort of LTX recipients. 5,13 In our present study, the prevalence of PF was 22%, CogF 28%, DepF 29%, and ComF 34% in patients on the LTX waitlist. Second, PF, low serum albumin, and MCI are independently associated with waitlist mortality.…”
Section: Discussionsupporting
confidence: 50%
“…PF was assessed using a modified version of the FFP to categorize patients as frail or nonfrail. Details of the modified assessment tool have previously been published 5,13 and are outlined in Table 1. The FFP assesses the following 5 physical domains: exhaustion, grip strength, gait speed, unintended weight loss, and physical activity.…”
Section: Methodsmentioning
confidence: 99%
“…33 Montgomery et al reported that pretransplant frailty was largely reversed in patients who undertook a 3-month rehabilitation program after lung transplantation. 35 Collectively, these reports suggest that following any major surgical intervention, frailty is likely to worsen in the first few months and that improvement of frailty status is unlikely to be observed within the first 3 months post-intervention. Although not directly addressed in this review, it is likely that other patient characteristics interact with frailty to contribute to postoperative morbidity and mortality.…”
Section: Effect Of Interventionmentioning
confidence: 97%
“…20 Similar findings with regard to reversal of frailty have been reported in patients undergoing kidney, liver, or lung transplantation. [33][34][35] In a study of 349 patients undergoing kidney transplantation, McAdams-DeMarco et al reported that for the study population as a whole, frailty status worsened over the 1st month posttransplant, returned to baseline in the 2nd month and improved 3 months post-transplant. 34 In 2017, Lai et al reported that frailty status deteriorated in liver transplant recipients over the 3 months post-transplant before improving modestly by 12 months.…”
Section: Effect Of Interventionmentioning
confidence: 99%